Validity of Assessment Instruments for Evaluating the Feasibility of Developing an Integrated STEM Inquiry Model in 21st-Century Education - Isnaini Isnaini; Atmazaki Atmazaki; Yuni Ahda; Suci Fajrina (Jurnal Ilmiah Pendidikan Fisika, 2025)
The validity of assessment instruments is a crucial element in educational research, particularly in evaluating the success of a learning model. In developing an integrated STEM inquiry learning model, it is necessary first to validate the assessment instruments to ensure they can effectively measure the desired learning outcomes, including both academic knowledge and the 21st-century skills developed by students. This study evaluates the validity of the instruments used to assess the feasibility of the integrated STEM inquiry model, which includes the model book, teacher's book, student's book, and a 21st-century skills assessment instrument. The instruments were validated through expert judgment involving three validators: an educational expert in evaluation, a STEM curriculum developer, and a language and communication practitioner. The instruments were assessed using a five-point Likert scale, and the data were analyzed using descriptive statistics to determine content, construct, and criterion validity. The results show that the 21st-century skills instrument scored 0.89, the model book scored 0.84, the student book scored 0.87, and the teacher book scored 0.86, all falling into the very high validity category. These findings indicate that the instruments are appropriate and reliable for measuring both academic competencies and essential 21st-century skills such as problem-solving, creativity, and collaboration. The study concludes that employing valid assessment instruments is essential for the effective implementation of the integrated STEM inquiry model and for ensuring its success in fostering the holistic development of students. The findings also highlight the importance of instrument validation in educational settings to ensure that learning models achieve their intended outcomes and prepare students for future challenges.